BENTHIC MACROINVERTEBRATE COMMUNITIES AND ITS DIVERSITY IN TAMASI LAKE, TEHSIL- BHADRAVATI, DISTRICT-CHANDRAPUR(M.S.) - Tekade Rita Sharad rao,; Telkhade Pravin Madhukar rao, (The Bioscan, 2025)
Benthic macroinvertebrates are a bioindicator forevaluating overall health of aquatic ecosystem and the quality of water. Change in environmental factors reflected in the structure of benthic macroinvertebrate community. Study was carried out during May 2022 to April 2023 at Tamsi Lake Tahsil- Bhadravati District – Chandrapur. In presentinvestigation total of 23 macroinvertebrates species were recorded and identified, belonging to 11Order from all the study sites. Benthic population size and distribution were showing spatial effect. Climatic effect has shown a considerable difference in the number of benthic communities. In comparison to the dry season, more individuals were seen during the wet season. The Hemiptera family species of macroinvertebrates showed their maximum appearance, followed by Diptera, Coleoptera and Gastropoda. Less number of animals representing the order Ephemeroptera, Tubificida and Glossiphoniiformes were identified. When compared the presence of bioindicator species at the majority of sampling sites, the Benthic community of Tamasi lake shows tolerant species. This indicates the existence of pollution and hence is likely to undergo environmental stress.